Beragama di Era Digital: Aktivisme Pemuda Gereja dalam Praktik Misa Online - Dionisius Krisna Anggriawan; Elya Kurniawati; Ahmad Arif Widiyanto (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The Covid-19 pandemic brought a rapid flow of change to various lines of life including worship activities. Digital services in the form of Online Mass are present as a solution for Catholics. A big question arises whether the Online Mass is really a mass, and can bring a complete imagination to the people who are following the Eucharistic Celebration. The purpose of this study is: (1) to find out the form of ministry provided by the Parish Catholic Church of Saint Albert deTrapani to the people in the midst of the Covid-19 pandemic, (2) Knowing the form of imagination experienced by Catholic Parishioners of Saint Albertus de Trapani in attending the Online Mass. This study uses the theory of social construction Peter L. Berger and Thomas Luckmann by using qualitative research methods descriptively based on data findings in the field with purposive sampling techniques where informants are determined based on their role and association to the Online Mass there are 3 criteria, namely: (1) Father, (2) Youth Church, (3) Ummah.  The study was conducted from October to December. The result of this research is that in the midst of the Covid-19 Pandemic situation, St. Albert deTrapani Church is increasingly actively providing digital services to its people through some digital content. Mass Online became a solution in the midst of the Covid-19 pandemic but could not replace the religious meaning of Mass directly.